Exploring Sustainable Procurement Practices in Public Procurement: A Case Study of University of Health and Allied Sciences-Ho. - Sakyi, Kwabena (2016)
A Thesis submitted to the Department of Building Technology, College of Art and Built Environment in partial fulfilment of the requirements for the degree of Masters of Science.